Irish songs of resistance [Bladmuziek]. ([S.l.] : [s.n.])
Deze publicatie bevat volgende liederen
Wrap the green flag round me, boys
God save Ireland
The Bold Fenian Men
Sean Sabhat of Garryowen
Boolavogue
The foggy Dew
The Mountains of Pomeroy
Henry Joy
Gradh mo chroidhe, I long to see old Ireland free once more
The dying Rebel
The West's Awake
Sean Treacy
The Rifles of the IRA
The Boys of Wexford
Tone's Grave
Roddy McCorley
Banna Strand
Take it down from the Mast
James Connolly
The rising of the Moon
The Wind that shakes the Barley
Come to the Bower
The Jackets green
Old Skibbereen
Kelly of Killanne
Belfast Brigade
Brave Tom Williams
The old Fenian Gun
Ireland divided
A Nation once again
The Memory of the Dead
Ashtown Road
The croppy Boy
Kevin Barry
Upton Ambush
The green and the white and the gold
A Soldier's Song
Archief Wim Wabbes
Engels
Bladmuziek
Keywords: liederen